SHEEP HOUSING AND HEALTH MANAGEMENT AT JOGLO FARM DRAMAGA BOGOR - Dhifa Hilmi Fauzan; Dede Kardaya; Ristika Handarini (Ann Publisher, 2024)
The health of sheep is an important factor and can affect sheep production. Livestock health handlers include health handling, hoof cutting, cage disinfection, ectoparasite control, vaccine administration, and deworming. This activity aims to compare the knowledge gained in lectures and their application in the field related to housing management and sheep health. This activity was held at Joglo Farm for a month, from August 13, 2022, to September 13, 2022—observation and interview methods. This activity showed that sheep health management on the Joglo farm was quite good because the maintenance procedures were exceptionally complete and regular